Pengaruh Keunikan Atribut Produk Terhadap Keputusan Konsumen Dalam Memilih Produk Minuman Teh Botol Sosro - Sartika, Dewi; , Dr. Anton Agus Setyawan, SE., M.Si (2015)
The primary concern of this research is knowing and analyzing the influence significant atribute product that consist of package, taste, volume, product's content and its serve toward decision of purchasing Teh Botol Sosro beverage and which variable is more dominant to influence this based on its variable atribute. This file research is collected by questioning and measured by Likert scale. Meanwhile the sample that will be taken is about 150 (one hundred and fifty) corespondences of Teh Botol Sosro consumer. According to the analyzing of age corespondence result derives from variable package, multi taste, volume, product's content and its serve, the age under twenty years old, while based on the gender of corespondence, female are more dominant than male